Turkic- Slavic- German contacts in diachrony: cultural- paradigm language (Eurasian Journal of Philology Science and Education, 2016)
The logical consequence of language contact is the borrowing – one of the oldest and natural sources of replenishment of the vocabulary of the language. Borrowing the words we borrow items and foreign culture, while identifying their need and importance in our lives.This article deals with the language and cultural interaction of Turkic, Slavic and German peoples. We consider some moments borrowed adaptation of units, in particular, their grammatical form and thematic classification.
Keywords: linguistic interaction; cultural exchange; adaptation of grammatical borrowing.